Epidemiological changes in Chlamydia pneumoniae molecular detections before, during and after the COVID-19 pandemic in 27 European sites and Taiwan, 2018 to 2023 - on behalf of the ESCMID Study Group for Mycoplasma and Chlamydia infections (ESGMAC) (Eurosurveillance)
Background During the COVID-19 pandemic, non-pharmaceutical interventions (NPIs) such as social distancing, lockdowns and enhanced hygiene led to a decrease in respiratory pathogens. However, as NPIs were relaxed, a resurgence in several respiratory pathogens was observed including one local Chlamydia pneumoniae outbreak in Switzerland, prompting the need for a better understanding of C. pneumoniae epidemiology. Aim To assess temporal and geographical variations in C. pneumoniae detection before, during and after the COVID-19 pandemic. Methods Data on C. pneumoniae PCR detection ratios (number of positive tests/ total number of tests) across pre-pandemic (2018–2019), pandemic (2020–2022) and post-pandemic (2023) periods were collected via a global survey disseminated through various professional networks. Results C. pneumoniae detection ratios were analysed across 28 sites (27 in Europe, one in Taiwan) in 2023 (Dataset A, n = 172,223 tests) and 20 sites from 2018 to 2023 (Dataset B, n = 693,106 tests). Twenty-seven sites were laboratories (hospital or clinical) and one a surveillance system (Denmark). A significant decrease in detection ratios was observed during the pandemic period (from 1.05% to 0.23%, p < 0.001). In 2023, detection ratios increased to 0.28% (p < 0.002). Notable regional variations were found, with statistically significant increases in detection ratios at six sites located in Switzerland and Slovenia, where ratios ranged from 0.52% to 3.25%. Discussion The study highlights how NPIs influenced C. pneumoniae epidemiology, with reduced detection during the pandemic and partial resurgence afterwards. Regional variations suggest differing NPI impacts and underscore the need for continued surveillance.